Modified Diagnostic Methods For The Treatment Of Children With Narrowing Of The Upper Jaw And Impaired Nasal Breathing (Journal of Pharmaceutical Negative Results, 2023)
Not much attention has been paid to the identification of morphological changes in the face-jaw area in children with chronic diseases of the respiratory system. Orthodontic dentist, ENT, pediatric specialists did not work together. In order to eliminate anomalies and deformations of the tooth-jaw system, orthodontic dentists carried out treatment measures without paying attention to their etiology. Today, attention has been paid to the treatment of changes in the face-jaw area in children with chronic diseases of the respiratory system, anomalies and deformations of the tooth-jaw system. Analysis of morphological changes in the upper jaw in mouth-breathing children, clinical examinations, anthropometric analysis of control diagnostic models separately for each patient, as well as analysis of X-ray data (orthopantomography and teleroentgenography). Evaluating the economic and medical effectiveness of our research.